Banyuurip Village Community Empowerment Strategy Based on the Sustainable Livelihood Approach - Dwi Prasetyo, Irwan; Putri Ayu , Anita (Riviera Publishing, 2024)
This study outlines the main findings from the Social Mapping activities that have been carried out in the work area of Saka Indonesia Pangkah Limited (SIPL) in Gresik Regency, namely in Banyuurip Village which then conducted a Sustainability Livelihood Approach (SLA) study to find out 5 main capital or assets, namely 1.) Natural Resource Capital, 2.) Human Resource Capital, 3.) Social Capital, 4.) Financial Capital, and 5.) Infrastructure Capital. This study uses a mixed method methodology, a combination of quantitative methods and qualitative methods whose data collection was carried out in January 2024 through 100 respondents. The quantitative method is carried out through survey activities using questionnaires as data collection instruments, while data processing is carried out using statistical software, namely SPSS (Statistical Package for the Social Sciences) as an analysis tool. by purposive sampling and snowball method. The results of this study show that the economic growth of the community in Banyuurip Village largely depends on the aspect of natural resources where the community can obtain it from marine and coastal catches.